A general model to predict germination and safe storage time of crop seeds. (December 2022) - Jian, Fuji
Abstract: To safely store grain seeds, the safe storage time under different storage conditions should be estimated. A general model to predict the safe storage time of cereal grain (durum wheat, wheat, and rye) and oilseed (canola and hemp seeds) was developed by using measured germination data and mould growth rates in stored grain bulks reported in literature. The reported germination and mould growth rates in literature were measured under different constant temperatures and water activities or grain moisture contents. The model was developed by considering the effect of fungal multiplication and interaction of biotic and abiotic factors on germination loss. The developed models could predict the germination and safe storage time of the examined crops (durum wheat, wheat, rye, canola, and hemp seeds). Average values of the absolute difference between measured and predicted germination of the examined crops in this study was less than 17.3 percentage points. For any crop, the difference between measured and predicted safe storage times (residue) was usually less than 10 d. The model developed for durum wheat could be used to predict the germination and safe storage time of wheat and rye. The maximum value of the absolute difference between measured and predicted germination associated with the rye was 2.1–13.6 percentage points, while it was 6.9–17.3 for durum wheat. The residues associated with durum wheat also had a wider interquartile range than that of rye. Therefore, the developed model could be used as a tool to compare the storability of different crops and varieties with different initial germinations under different storage conditions. Highlights: A general model was developed to predict safe storage time of stored grain. The model considered the effect of biotic and abiotic effect on germination loss. Equation for the effect of mould growth on any examined crop was the same. The difference between measured and predicted safe storage time was ≤10 days. The model developed for durum wheat could be used for wheat and rye.